Support from start to finish—a collaborative primary medical program in rural Victoria, Australia - Will Harvey; Lachlan Van Schaik; Tamekha Develyn; Zahra Ali; Cathryn Hogarth; Julian Wright (Frontiers in Medicine)
Australia faces a persistent shortage of doctors in rural and regional areas, exacerbating health disparities between urban and rural communities. Traditional medical education models, which have been largely centralized in metropolitan areas, often result in rural-origin students needing to relocate to cities for training, thus disrupting community connections and reducing the likelihood of their return to rural practice. To address this challenge, the University of Melbourne and La Trobe University have collaborated to establish Victoria’s first end-to-end rural medical pathway, an innovative model that enables students to complete both their undergraduate [“Bachelor of Biomedical Science (Medical)”] and Doctor of Medicine (MD) entirely within regional and rural settings. This paper explores the implementation, practical considerations, and evaluation mechanisms of the end-to-end rural medical pathway, highlighting its place-based curriculum, and fully distributed medical education model. Although this program is yet to be evaluated, it is intended that by embedding students in primary care clinics and regional hospitals throughout their training, the program will foster long-term professional and personal ties to rural communities. This initiative represents a scalable and evidence-based model for addressing rural medical workforce shortages, offering insights that could inform national and international medical education policy.